SECURITY CHALLENGES IN MOBILE ASSISTED LANGUAGE LEARNING IN THE MILLENNIUM FOR EDUCATION - Soleimani, Hassan; Rostami Abu Saeedi, Ali Asghar; Rahmanian, Mahboubeh (Advanced Education, 2016)
Distance learning technologies enrich learning opportunities due to many advantages like ubiquity and flexibility. Although the usefulness of such technologies in teaching and learning is clear, their testing part is remained to be discussed due to the security issue. Administrators and teachers need to use more authentic and secure distant testing software in which the scores are guaranteed and the testees keep away from cheating. Static and online authentication systems like “username” and “password” and face detection have empowered educational parties to have more reliable testing outcomes. Mobile devices as the necessity of the new millennium need to use authentication software in their testing. Mobile devices with their multimedia course materials provide learners with many optimistic learning opportunities through collaboration, cooperation, interaction and testing. The unique chances of ubiquity, individualization, informality, and spontaneity make the mobile learning of particular importance not only for digital natives but also for teachers, administrators, developers, instructors, and policy makers. Yielding an economical learning opportunity along with providing authentic contexts for collaborative learning is beneficial for the economy of the country in general and for the meaningful and deep learning of the learners. This paper will discuss how authentication techniques have applied to electronic devices like mobile phones.